An electrochemical and leach study of the oxidative dissolution of chalcopyrite in ammoniacal solutions - Moyo, Thandazile (Centre for Minerals Research, 2017)
Chalcopyrite is not only the most abundant of the copper sulphides, but also the most stable, making it recalcitrant to hydrometallurgical treatment processes especially in atmospheric leaching. Hence, pyrometallurgical processes are traditionally used to treat chalcopyrite concentrates. However, ore grades are falling and concentration processes are becoming increasingly costly, prompting need to revisit hydrometallurgical treatment processes (especially heap leaching), which are otherwise regarded as relatively economic and environmentally friendly. Key hydrometallurgical processes for chalcopyrite treatment are ferric sulphate, chloride and ammoniacal systems. The ferric sulphate system does not work well under atmospheric conditions, except in combination with thermophilic microorganisms, whereas the chloride system has only recently been evaluated more seriously for heap leach processes. The ammonia system remains relatively unexplored and most studies date back more than 40 years, but the system has considerable potential for further development. Ammonia systems can be effectively used to leach copper from chalcopyrite in the presence of an oxidant. The ammoniacal leaching system is heavily reliant on a good surface mass transfer system, hence it being widely studied in high pressure systems where oxygen was accepted to be the oxidant. Leach reactors were designed to use agitation systems which promote the abrasion of an iron based deposit layer thought to passivate the mineral surface. Most research on the ammonia leaching systems has previously been carried out in controlled or bulk leaching studies and only a few used electrochemical studies. A disconnect exits between the two approaches, resulting in different proposed fundamental reaction mechanisms and kinetic understanding. A fundamental electrochemical and controlled leach study of the oxidative leaching of chalcopyrite in ammoniacal solutions has been undertaken. The study covered the following aspects: a description of the mixed potentials, chemistry and kinetics of the anodic reaction, the cathodic reduction of the oxidants, the formation and effect of surface deposits and lastly a look at how results from electrochemical studies compare to those from the leaching of a similar mineral sample under similar solution conditions. A detailed study of the mixed potentials on a more or less pure chalcopyrite electrode has shown the redox reactions on the surface of the mineral to be controlled by the oxidation of chalcopyrite and reduction of copper(II). The presence of oxygen has been found to have no significant effect on mixed potentials in ammoniacal solutions in the presence of initial copper(II). Constant potential and potentiodynamic studies on the anodic reaction have shown the rate of the anodic reaction to increase with an increase in potential in a standard 1M ammonia/ammonium sulphate solution (which buffers at pH 9.6) in exponential fashion supporting conventional Butler-Volmer behaviour with a anodic transfer coefficient of 0.42 and a rate constant k* CuFeS2 of 0.0431 cms⁻¹. Increasing total ammonia increased the rate of reaction only at low concentrations; at higher concentrations increasing total ammonia had no effect on the anodic reaction. An increase of pH at fixed total ammonia concentration showed an increase in reaction rate, but the effect cannot clearly be discerned from the concomitant shift in relative proportion of free NH₃ and NH₄⁺. Coulometric studies have shown the oxidation reaction to proceed via the formation of a thiosulphate intermediate and this to be a 7-8 electron transfer reaction. A surface deposit layer consisting of iron, oxygen and small quantities of sulphur was formed and the sulphur component of this product layer was seen to be gradually depleted during leaching. Anodic currents were found to gradually decrease with time and this was linked to the growth of the surface deposit layer. However, the surface deposit layer did not passivate the anodic reaction; instead, it was proposed that the surface deposit layer adsorbed copper ions and displayed "ohmic" behaviour. The formation of the surface deposit layer was found to apparently promote the cathodic reduction of copper(II). While reduction of copper(II) was shown to be the primary reduction reaction, the presence of oxygen was seen to promote this reduction reaction through the regeneration of copper(II) in experiments that ran for longer time periods. An apparent accumulation of copper(I) on the mineral surface was seen to adversely affect the rate of the cathodic reaction and thus the overall rate of dissolution. The nature and morphology of the surface layer was found to be significantly influenced by the choice of cation in solution, which was thought to influence primarily the complexation/precipitation of ferric species forming near the surface. The degree of agitation during leach studies influences the rate of leaching due to the fragmentation of surface deposits, which are seen to slow the anodic reaction. A kinetic model has been developed for the anodic and cathodic reactions. This thesis presents significant new findings regarding the role of the copper(I)/copper(II) redox couple on the oxidative leaching of chalcopyrite. It also highlights the potentially limiting role of the cathodic reactions which have frequently been overshadowed by the focus on chalcopyrite oxidation reactions. Furthermore, the growth of a surface inhibiting layer which cannot be removed in heap leach systems due to the lack of mechanical agitation can now potentially be addressed by looking into the complexation and precipitation characteristics of cations in solution for ammoniacal leach systems.